Analisis Kesulitan Siswa Kelas X SMAN I Rejotangan pada Materi Bentuk Akar dan Solusi yang Ditawarkan - Albadawi, M. Haris; Zulfa, Hariratuz; Sumani, Sumani (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
Mathematics is a subject that is considered difficult by students. This assumption is not without reason, because Mathematics is a structured science. If the student does not have a structure, then he will not be able to build a structure on it. Many difficulties are commonly experienced by students in Mathematics subjects. Usually students have difficulties in understanding the concept, application of principle, miscalculation, and less skilled in operation. Researchers chose SMAN I Rejotangan for research. This school is still using the curriculum KTSP when researchers conduct research. This school is easily accessible because it is located on bus lane. In addition, researchers also become educators at this school. Therefore, researchers know very well the atmosphere in this school. When conducting National Exam preparation guidance in class XII, researchers found many mistakes from students when working on root shape issues. While the material of the root form should have been mastered by students since class X. Therefore, there must be something that happens when students are still sitting in the bench class X. For various reasons this researcher want to reveal the reason behind the mistakes of students in working on the form of the root form. Not just to analyze students' mistakes, but also to find out the causes of students making.